IMPLEMENTASI AKAD MUSYARAKAH PADA PEMBIAYAAN USAHA MIKRO DI PT. BANK PERKREDITAN RAKYAT SYARIAH BAROKAH LAMPUNG - Ditta Nur Hidayanti (Institut Agama Islam Agus Salim Metro Lampung, 2022)
This study aims to describe the implementation of Musyarakah contracts in micro business financing and explain the analysis of the implementation of Musyarakah Contract Financing at PT. BPRS BDS in Islamic Economic Perspective. The type of research used is field research. In this study the method used included three interactive activities consisting of data reduction (data simplification), data presentation and drawing conclusions and verification. Dataanalysis used qualitative data analysis techniques by means of inductive thinking. Based on the results of research conducted at PT. BPRS BDS regarding the Implementation of Musyarakah Contracts in Micro Business Financing is actually good, and has referred to the provisions of the DSN MUI fatwa regarding musyarakah contract financing. In the analysis of the provision of financing PT. BPRS BDS also uses the 5C principles (Character, capacity, Capital,Conditional and Collateral). PT. BPRS BDS in providing financing must use collateral as a binder. Loss sharing at PT. BPRS BDS is only borne by the mudharib